2015
DOI: 10.5194/acp-15-11653-2015
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anthropogenic dust using CALIPSO lidar measurements

Abstract: Abstract. Anthropogenic dusts are those produced by human activities on disturbed soils, which are mainly cropland, pastureland, and urbanized regions, and are a subset of the total dust load which includes natural sources from desert regions. Our knowledge of anthropogenic dusts is still very limited due to a lack of data. To understand the contribution of anthropogenic dust to the total global dust load, it is important to identify it apart from total dust. In this study, a new technique for distinguishing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 65 publications
6
102
0
Order By: Relevance
“…This assumption is consistent with the results of a recent study by Huang et al (2015a), who found that anthropogenic dust comprises 91.8% of regional emissions in eastern China and 76.1% of regional emissions in India (e.g., Figure 10 in Huang et al, 2015a). 5…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…This assumption is consistent with the results of a recent study by Huang et al (2015a), who found that anthropogenic dust comprises 91.8% of regional emissions in eastern China and 76.1% of regional emissions in India (e.g., Figure 10 in Huang et al, 2015a). 5…”
Section: Introductionsupporting
confidence: 81%
“…This may be due to the larger population densities of eastern China and India, which are characterized by intense human activity (Huang et al, 2015a;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the anthropogenic regions of eastern China, anthropogenic particles originating from human activities are expected to comprise more than 90 % of dust particles (Huang et al, 2015a). When the westerly winds are strongly blowing over the Noto Peninsula, the black carbon particles at upper altitudes (3000 m) are thought to mainly derive from continental anthropogenic regions.…”
Section: Aerosol Dynamics During Asian Dust and Non-dust Eventmentioning
confidence: 99%